2018
DOI: 10.1016/j.ajem.2017.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bronchodilator administration with vibrating mesh nebulizer and standard jet nebulizer in the emergency department

Abstract: The VMN was associated with fewer admissions to the hospital, shorter length of stay in the ED and a reduction in albuterol dose. The device type was a predictor of discharge, disposition and amount of drug used. Randomized controlled studies are needed to corroborate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 16 publications
1
34
0
8
Order By: Relevance
“…22 The holding chamber significantly increased (P Ͻ .001) the aerosol emitted to double from the Solo. 5 Also, the use of the holding chamber with a jet nebulizer significantly increased (P Ͻ .01) the aerosol emitted to double that of the jet nebulizer-T-piece. These results extended the benefit of the tested holding chamber as an aerosol saver to the jet nebulizer.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…22 The holding chamber significantly increased (P Ͻ .001) the aerosol emitted to double from the Solo. 5 Also, the use of the holding chamber with a jet nebulizer significantly increased (P Ͻ .01) the aerosol emitted to double that of the jet nebulizer-T-piece. These results extended the benefit of the tested holding chamber as an aerosol saver to the jet nebulizer.…”
Section: Discussionmentioning
confidence: 94%
“…24 The Solo-holding chamber resulted in much better delivery than the Pro and the jet nebulizer or even the Solo itself with its T-piece. 5,25 These results might have occurred because the holding chamber studied was designed for the Solo, with which it gives maximum advantage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term use of different types of nebulizers might influence the outcome. Dunne and Shortt reported that use of MN was associated with fewer admissions to the hospital, shorter length of stay in the emergency department, and a reduction in total beta 2 agonist dose [11].…”
Section: Discussionmentioning
confidence: 99%